Incompetent memory immune response in severe COVID-19 patients under treatment - Shukla Das; Gargi Rai; Vikas Sood; Praveen Kumar Singh; Asha Tyagi; Rashmi Salhotra; Chhavi Gupta; Viniita Kumar Jaggi; Sajad Ahmad Dar; Mohammad Ahmad Ansari (Heliyon, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) associated coronavirus disease 2019 (COVID-19) pandemic has affected millions of people worldwide and declared a Public Health Emergency by the World Health Organization (WHO) on January 30, 2020. Albeit, unprecedented efforts have been made from the scientific community to understand the pathophysiology of COVID-19 disease, the host immune and inflammatory responses are not explored well in the Indian population. Continuous arrival of new variants fascinated the scientists to understand the host immune processes and to eradicate this deadly virus. The aim of this study was to see the helper and cellular host immune responses including memory and activated cell subsets of COVID-19 patients admitted to the intensive care unit (ICU) at different time intervals during the treatment. PBMCs separated from nine patients with SARS-CoV-2 infection were incubated with fluorescent conjugated antibodies and acquired on flow cytometer machine to analyze the T and B cell subsets. The results in COVID-19 patients versus healthy volunteers were as follows: elevated helper T cells (57.4% vs 44.9%); low cytotoxic T cells (42.8% vs 55.6%), and activated T (17.7% vs 21.2%) subsets. Both, TREG (40.15% vs 51.7%) and TH17 (13.2% vs 24.6%) responses were substantially decreased and high expression of TREG markers was observed in these patients compared with controls.